Comparison of the three forensic DNA Sampling and extraction techniques on various mock crime scene samples for reliable and rapid DNA analysis - Yee, Glenna Tan Jie (2022)
The capability to generate reliable DNA profiles rapidly via short tandem repeat (STR) analysis to identify the suspect could greatly assist in crime investigations. This study evaluated the performance of a compilation of sample collection and extraction techniques consisting of the Maxwell RSC 48 FSC DNA IQ Casework Kit, Casework Direct System, and the COPAN MicroFLOQ® Direct Swab. A total of 48 reactions consisting of 16 mock casework samples for each technique ranging from bloodstain, saliva stained and touch DNA samples that were commonly encountered in crime scene were used in this study. The samples extracted using the Maxwell RSC 48 FSC DNA IQ Casework Kit were quantified using the NanoDrop™ 2000 Spectrophotometer. Subsequently, the collected samples for the three techniques were amplified using the GlobalFiler™ Express PCR Amplification Kit. The amplified products were then loaded for capillary electrophoresis via the ABI 3500xL Genetic Analyzer before analyzed using the GeneMapper ID-X v1.4 software. Results demonstrated that the three techniques generated relatively high percentage of autosomal STR allele call in total (100%, 100% and 96% respectively). Particularly, the COPAN MicroFLOQ™ with 96% was possible to analyze wide range of DNA samples where seven out of 16 samples were typed successfully. Meanwhile, the same number of sample types (n=6) with 100% autosomal STR allele call percentage and full consistent profiles were generated via the extraction using the two extraction kits. Notably, the average peak height across the samples using the former extraction kit was the highest which attributed to the automated extraction and purification employed that corresponded to the high DNA concentration yielded. This were followed by Casework Direct System and COPAN MicroFLOQ . In terms of turnaround time and cost associated, the MicroFLOQ® Direct Swab outperformed the other two techniques followed by the Casework Direct System extraction which took one hour for complete extraction. Meanwhile, the Maxwell FSC DNA IQ Casework Kit which took a longer time and higher cost for the entire extraction (1 hour 30 minutes and average RM 76.15 per reaction respectively). Not to mention, the use of the kit coupled with the automated Maxwell RSC 48 instrument ( RM 450, 000 per instrument) were on the more expensive end as compared to the other two techniques. Overall, the three different techniques had their respective merits and pitfalls but the COPAN MicroFLOQ® Direct Swab had an edge over the other two methods in terms of time, cost-effectiveness and ease to use. It also offered numerous advantages due to its direct PCR amplification properties, relatively high detection ability and quality DNA profiles produced. This resulted in the COPAN MicroFLOQ® Direct Swab capable to generate DNA profiles reliably in a short time thus potentially become a novel preferable collection technique employed by law enforcement officers.